Method for preparing a grinding aid modified solid waste based low clinker cement
Patent Information
- Application Number
- CN202611323745.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明旨在解决现有的助磨剂添加工艺因忽略粉磨微环境演变规律而导致的固废活化程度受限的问题
1、在固废基少熟料水泥制备中,建立助磨剂作用时序与粉磨微环境热焓状态的动态关联,通过将研磨机械能转化形成的环境温度作为化学反应的触发基准,使第一助磨剂在达到活化温度阈值时注入粉磨设备,从而诱导工业固废表层的致密玻璃体网络发生深度解聚,消除激发组分在低温阶段产生的无效物理吸附,实现对固废内部潜在胶凝活性的深度激发。
Smart Images

Figure CN122916469A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid waste treatment technology, and in particular relates to a method for preparing solid waste-based low-clinker cement modified with grinding aid. Background Technology
[0002] Currently, the main technical direction is to activate the activity of bulk industrial solid waste and prepare low-clinker cement by using admixtures. Grinding aids are usually used to reduce the surface energy of materials and destroy the dense glassy structure inside the solid waste through mechanochemical action. The modification and activation process of the microscopic surface of solid waste is subject to dual constraints of thermodynamic and kinetic environmental evolution. The complexation reaction between chemically activated components and metal cations needs to overcome a specific thermodynamic energy barrier. This process depends on the heat energy converted from mechanical friction in the mill. Meanwhile, the agglomeration behavior of powder particles is concentrated in the middle and late stages of grinding when the specific surface area increases significantly.
[0003] Existing static addition processes lead to a mismatch in the timing of action. In the early stages of grinding, the low ambient temperature causes the activation component to suffer physical adsorption loss, failing to achieve effective bond breaking. In the later stages of grinding, the physically dispersed component and the activation component compete for adsorption on the newly formed cleavage surfaces, weakening the steric hindrance effect between particles. Even attempts to improve performance by increasing the dosage or using premixing processes often fail to balance grinding efficiency and activation depth due to reagent interference and increased costs. While hardware improvements such as grinding roller morphology and grinding media ratios have matured, existing technologies have shortcomings in the control aspects, such as grinding process control strategies and dosing timing logic. For example, [the following is a separate section, likely from a different source:] CN1 Chinese invention patent application 20136461A discloses a coal-based solid waste cementitious material, its preparation method, and its application for coal mine backfilling projects. The stability is improved by combining various coal-based solid wastes and subsequent acidification treatment with carbonizing gas. However, the grinding aid adopts a static addition mode, ignoring the dynamic evolution law of the lattice energy level and surface physicochemical properties of material particles during the conversion of mechanical energy into thermal energy in high-volume solid waste. The addition method, which is detached from the response of the microenvironment parameters inside the mill, causes the chemically excited components to undergo physical adsorption loss at low temperature. In the later stage of fine powder agglomeration, it cannot provide precise spatial steric hindrance locking, making it difficult to achieve deep lattice defect induction and locking while ensuring grinding efficiency.
[0004] Therefore, how to construct a process that dynamically adjusts the timing of component intervention based on changes in the microenvironmental parameters of grinding, thereby achieving deep activation of the coagulation activity of solid waste, is the technical problem to be solved by this invention. Summary of the Invention
[0005] The present invention aims to solve the problem that the activation degree of solid waste is limited due to the neglect of the evolution law of the grinding microenvironment in the existing grinding aid addition process.
[0006] In this technical solution, a method for preparing solid waste-based low-clinker cement modified with grinding aids includes the following steps: Step S101: Obtain industrial solid waste and silicate clinker in a predetermined mass ratio and feed them into a closed-circuit grinding system. Step S102: Start the closed-circuit grinding system to grind the material, and use the temperature sensor set at the outlet of the closed-circuit grinding system to collect instantaneous temperature data in real time, which characterizes the thermal state of the microenvironment of the material grinding. Step S103: Compare the instantaneous temperature data with the preset structural activation temperature threshold band of 85°C to 105°C. When the instantaneous temperature data reaches the structural activation temperature threshold band, add a first grinding aid containing an alcohol amine complex component into the closed-circuit grinding system to change the lattice structure of the fresh cleavage surface generated by industrial solid waste. Step S104: Collect the instantaneous specific surface area of material particles in the closed-circuit grinding system and the cumulative power consumption data of the main motor of the closed-circuit grinding system, and use this data to calculate the particle grinding efficiency factor that characterizes the dynamic evolution of grinding efficiency. Step S105: When it is determined that the particle grinding efficiency factor shows a monotonically decreasing state for three consecutive sampling cycles and the cumulative decrease exceeds 15%, a second grinding aid containing polycarboxylic acid dispersion components is added to the closed-circuit grinding system to inhibit the agglomeration behavior of fine powder by using the physical isolation layer generated on the surface of industrial solid waste particles by the second grinding aid. Step S106: Continue grinding until the specific surface area of the material at the outlet of the closed-circuit grinding system reaches 400 m². 2 / kg to 550m 2 The target range is between / kg.
[0007] Preferably, in step S103, the injection flow rate of the first grinding aid is adjusted according to the real-time rise slope of the instantaneous temperature data, and includes the following sub-steps: step S1031, measuring the temperature rise amplitude of the instantaneous temperature data per unit time and determining the corresponding thermal balance coefficient; step S1032, adjusting the metering pump frequency of the first grinding aid so that the addition rate of the first grinding aid matches the dissolution rate of the active components in the industrial solid waste.
[0008] Preferably, in step S101, the total weight of industrial solid waste and silicate clinker is 100 parts, including 60 to 85 parts of industrial solid waste and 15 to 40 parts of silicate clinker; the industrial solid waste includes granulated blast furnace slag powder, fly ash, steel slag powder and desulfurized gypsum.
[0009] Preferably, in step S103, the first grinding aid is injected through the spray atomization device of the closed-circuit grinding system, and its atomization pressure is controlled between 0.4MPa and 0.6MPa, so that the first grinding aid is uniformly covered on the fresh cleavage surface.
[0010] Preferably, in step S105, the second grinding aid includes a polycarboxylic acid dispersion component, polyethylene glycol, and lignin sulfonate; the second grinding aid neutralizes the residual charge on the surface of industrial solid waste particles through its polar functional groups, thereby blocking the interference between the adsorption positions of the first grinding aid and the second grinding aid on the fresh cleavage surface.
[0011] Preferably, in step S104, the instantaneous specific surface area is monitored by an online particle size analyzer, with data collected every 3 to 10 minutes, and includes the following sub-steps: comparing the particle size distribution in adjacent monitoring periods, calculating the slope of the uniformity coefficient change, in order to determine whether the material has entered the secondary agglomeration stage dominated by interfacial energy from the mechanical crushing stage.
[0012] Preferably, the closed-circuit grinding system includes a vertical mill or a ball mill; in step S102, the filling rate of the grinding media in the closed-circuit grinding system is controlled to be 25% to 35%, and the average residence time of the material inside the closed-circuit grinding system is controlled to be 25 min to 45 min.
[0013] Preferably, after grinding is completed in step S106, the obtained material is introduced into a cold air circulation device for rapid cooling, and the cooling rate is controlled to be no less than 15℃ / min, so that the active defect sites formed inside the industrial solid waste are physically locked when the temperature drops below 40℃.
[0014] Preferably, the cement product obtained meets the following performance requirements: 3-day compressive strength not less than 20 MPa, 28-day compressive strength not less than 42.5 MPa, and the 28-day hydration activity index of the industrial solid waste in it is not less than 85%.
[0015] Compared with existing technologies, the present invention provides a method for preparing solid waste-based low-clinker cement modified with grinding aids, which has the following advantages: 1. In the preparation of solid waste-based low-clinker cement, a dynamic correlation is established between the action sequence of grinding aids and the enthalpy state of the grinding microenvironment. By using the ambient temperature formed by the conversion of grinding mechanical energy as the triggering benchmark for chemical reaction, the first grinding aid is injected into the grinding equipment when it reaches the activation temperature threshold, thereby inducing deep depolymerization of the dense glass network on the surface of industrial solid waste, eliminating the ineffective physical adsorption of the activating components at low temperature, and realizing the deep activation of the potential gelling activity inside the solid waste.
[0016] 2. This scheme identifies the physical critical point at which the powder transitions from the mechanical crushing stage to the secondary agglomeration stage dominated by interfacial energy by real-time monitoring of the material's specific surface area evolution rate or coarse powder reflux increment rate. Based on this, it triggers the injection of a second grinding aid with a steric hindrance effect, thereby blocking the competitive adsorption interference between the activating component and the dispersing component on the newly formed cleavage surface of the particles. This allows the dispersing component to be fixedly coated on the surface of the activated fine particles, sealing the previously accumulated chemical reactivity inside the powder.
[0017] 3. This tiered intervention mechanism transforms the traditional static composite modification into a dynamic reconstruction process based on adaptive physical field parameters. Through the induction of solid waste lattice defects in the first stage and the physical locking of highly active surfaces in the second stage, a synergistic enhancement effect is generated, enabling the obtained solid waste-based cement powder to have high early hydration reaction potential. This effectively solves the problem of early strength cliff-like decline caused by the introduction of large amounts of solid waste in low clinker cement systems. Attached Figure Description
[0018] Figure 1 This is a process flow diagram of the preparation process of solid waste-based low-clinker cement with grinding aid modified in stages according to the present invention; Figure 2 This is a block diagram of the dynamic control logic for the grinding aid injection of the grinding efficiency factor in this invention. Detailed Implementation
[0019] The technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application are within the scope of protection of this application.
[0020] It should be noted that all directional and positional terms used in this invention, such as: up, down, left, right, front, back, vertical, horizontal, inner, outer, top, low, lateral, longitudinal, center, etc., are only used to explain the relative positional relationship and connection between components in a specific state (as shown in the accompanying drawings). They are only for the convenience of describing this invention and do not require that this invention be constructed and operated in a specific orientation. Therefore, they should not be construed as limiting this invention. In addition, the descriptions of "first," "second," etc., in this invention are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly indicating the number of technical features indicated.
[0021] In the description of this invention, unless otherwise explicitly specified and limited, the terms installation, connection, and linking should be interpreted broadly. For example, they can refer to fixed connections, detachable connections, or integral connections; they can refer to mechanical connections; they can refer to direct connections or indirect connections through an intermediate medium; they can refer to the internal connection of two components. For those skilled in the art, the specific meaning of the above terms in this invention can be understood according to the specific circumstances.
[0022] In the description of this specification, references to the terms "an embodiment," "some embodiments," "illustrative embodiments," "examples," "specific examples," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example, and the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0023] A method for preparing solid waste-based low-clinker cement modified with grinding aids includes the following steps: Step S101: Obtain industrial solid waste and silicate clinker in a predetermined mass ratio and feed them into a closed-circuit grinding system. Step S102: Start the closed-circuit grinding system to grind the material, and use the temperature sensor set at the outlet of the closed-circuit grinding system to collect instantaneous temperature data in real time, which characterizes the thermal state of the microenvironment of the material grinding. Step S103: Compare the instantaneous temperature data with the preset structural activation temperature threshold band of 85°C to 105°C. When the instantaneous temperature data reaches the structural activation temperature threshold band, add a first grinding aid containing an alcohol amine complex component into the closed-circuit grinding system to change the lattice structure of the fresh cleavage surface generated by industrial solid waste. Step S104: Collect the instantaneous specific surface area of material particles in the closed-circuit grinding system and the cumulative power consumption data of the main motor of the closed-circuit grinding system, and use this data to calculate the particle grinding efficiency factor that characterizes the dynamic evolution of grinding efficiency. Step S105: When it is determined that the particle grinding efficiency factor shows a monotonically decreasing state for three consecutive sampling cycles and the cumulative decrease exceeds 15%, a second grinding aid containing polycarboxylic acid dispersion components is added to the closed-circuit grinding system to inhibit the agglomeration behavior of fine powder by using the physical isolation layer generated on the surface of industrial solid waste particles by the second grinding aid. Step S106: Continue grinding until the specific surface area of the material at the outlet of the closed-circuit grinding system reaches 400 m². 2 / kg to 550m 2 The target range is between / kg.
[0024] Preferably, in step S103, the injection flow rate of the first grinding aid is adjusted according to the real-time rise slope of the instantaneous temperature data, and includes the following sub-steps: step S1031, measuring the temperature rise amplitude of the instantaneous temperature data per unit time and determining the corresponding thermal balance coefficient; step S1032, adjusting the metering pump frequency of the first grinding aid so that the addition rate of the first grinding aid matches the dissolution rate of the active components in the industrial solid waste.
[0025] Preferably, in step S101, the total weight of industrial solid waste and silicate clinker is 100 parts, including 60 to 85 parts of industrial solid waste and 15 to 40 parts of silicate clinker; the industrial solid waste includes granulated blast furnace slag powder, fly ash, steel slag powder and desulfurized gypsum.
[0026] Preferably, in step S103, the first grinding aid is injected through the spray atomization device of the closed-circuit grinding system, and its atomization pressure is controlled between 0.4MPa and 0.6MPa, so that the first grinding aid is uniformly covered on the fresh cleavage surface.
[0027] Preferably, in step S105, the second grinding aid includes a polycarboxylic acid dispersion component, polyethylene glycol, and lignin sulfonate; the second grinding aid neutralizes the residual charge on the surface of industrial solid waste particles through its polar functional groups, thereby blocking the interference between the adsorption positions of the first grinding aid and the second grinding aid on the fresh cleavage surface.
[0028] Preferably, in step S104, the instantaneous specific surface area is monitored by an online particle size analyzer, with data collected every 3 to 10 minutes, and includes the following sub-steps: comparing the particle size distribution in adjacent monitoring periods, calculating the slope of the uniformity coefficient change, in order to determine whether the material has entered the secondary agglomeration stage dominated by interfacial energy from the mechanical crushing stage.
[0029] Preferably, the closed-circuit grinding system includes a vertical mill or a ball mill; in step S102, the filling rate of the grinding media in the closed-circuit grinding system is controlled to be 25% to 35%, and the average residence time of the material inside the closed-circuit grinding system is controlled to be 25 min to 45 min.
[0030] Preferably, after grinding is completed in step S106, the obtained material is introduced into a cold air circulation device for rapid cooling, and the cooling rate is controlled to be no less than 15℃ / min, so that the active defect sites formed inside the industrial solid waste are physically locked when the temperature drops below 40℃.
[0031] Preferably, the cement product obtained meets the following performance requirements: 3-day compressive strength not less than 20 MPa, 28-day compressive strength not less than 42.5 MPa, and the 28-day hydration activity index of the industrial solid waste in it is not less than 85%.
[0032] Example 1: In a low-clinker cement production scenario where carbon emission reduction quotas are limited and there is an urgent need to utilize large quantities of industrial steel slag, when the system faces the dilemma of extremely low early hydration activity caused by the dense iron-rich glassy coating of steel slag, and the production collapse caused by the severe agglomeration of fine powder in the later stage of grinding, the timing of solid waste cementitious activity activation is reconstructed by deconstructing the grinding thermal environment and interface evolution dynamics. In the preparation process of solid waste-based low-clinker cement, 75 parts by weight of industrial steel slag and 25 parts by weight of silicate clinker are obtained and fed into a closed-loop grinding system. A temperature sensor is set at the outlet of the grinding equipment to collect instantaneous temperature data characterizing the thermal state of the material grinding environment. When the instantaneous temperature of the material is detected to cross the lower limit of the structural activation temperature threshold band of 85°C to 105°C, the first dosing pump injects chemicals into the grinding equipment at 0... A first grinding aid containing an alcoholamine complex component is atomized and injected at a dosage of 0.02%. The thermodynamic energy provided by this temperature range assists the mechanical force in overcoming the chemical bond breaking energy barrier, causing the alcoholamine functional groups to undergo in-situ chemical complexation reactions on the fresh cleavage surfaces of the steel slag. This induces lattice deagglomeration by extracting iron and aluminum cations from the glass network framework. During this injection process, the system extracts the first derivative of the instantaneous temperature data in real time as a thermo-mechanical balance coefficient characterizing the endothermic reaction of bond breaking in the solid waste network. Based on the preset apparent chemical reaction kinetic equation, the system linearly maps this temperature rise coefficient to the estimated value of the microscopic dissolution rate of iron and aluminum cations. Accordingly, the system simultaneously uses a frequency converter to adjust the output frequency of the first dosing pump to ensure that the effective supply of alcoholamine functional groups and the exposure of iron and aluminum cations remain dynamically consistent on a macroscopic control scale.
[0033] As the particle size decreases to the micrometer level, the specific surface area increases. The system collects the specific surface area of the particles every 5 minutes using an online particle size analyzer and calculates the particle grinding efficiency factor by combining it with the cumulative power consumption data of the main motor. The specific calculation logic is as follows: the difference in specific surface area between two adjacent sampling cycles is used as a characterization of the newly formed interface energy of the material, and it is divided by the incremental energy consumption of the main motor of the system within the same time span. This ratio is the particle grinding efficiency factor driven by both specific surface area and power consumption, used to quantify the effective newly formed cleavage surface area generated per unit of mechanical energy consumed. When the efficiency factor shows a monotonically decreasing trend for three consecutive sampling cycles and the cumulative decrease reaches the physical critical point of 18%, the system enters the fine powder agglomeration stage dominated by surface free energy, and the second dosing pump is started to inject the powder at a dosage ratio of 0.03% containing... The second grinding aid of polycarboxylic acid dispersion component utilizes the long side chain structure of polycarboxylic acid to construct a three-dimensional steric barrier layer on the surface of deformed solid waste particles, blocking the van der Waals force-induced contact between high surface energy particles, thereby sealing the accumulated chemical reactivity inside the powder. After completing the above grinding process, the obtained material is quickly introduced into a cold air circulation device for cooling at a rate of not less than 15°C / min. When the macroscopic temperature of the powder drops below 40°C, the polycarboxylic acid polymer chain segments coated on the surface of the solid waste particles undergo conformational contraction and phase solidification due to the drastic reduction of thermal motion, forming a rigid polymer physical coating layer. This rigid coating layer directly isolates the air medium and delays the premature hydration of the damaged microscopic lattice defects through physical shielding, thereby achieving long-term physical locking of internal active defect sites at the macroscopic level.
[0034] The final solid waste-based cement had a specific surface area of 510. The measured 3-day compressive strength was 24.5 MPa, and the 28-day hydration activity index reached 92%. This stepwise intervention method based on thermodynamic thresholds and kinetic inflection points solved the mismatch problem between the timing of admixture action and the evolution of the grinding environment. This was achieved by defining a formula for the modified activation index. The contributions of temperature and specific surface area increment to the active transitions were revealed, among which, The activation index is the modified value. For the increase in specific surface area, The activation energy of the structure The gas constant is... This refers to the instantaneous temperature during grinding.
[0035] Example 2: In a solid waste-based cement demonstration production line with an annual output of 1.205 million tons, a closed-circuit grinding test platform equipped with a dual-sensor redundancy system was used to simulate the grinding conditions of high-volume steel slag. The core verification parameters were set based on the constraint relationship between excitation energy consumption and excitation efficiency. Specifically, the sampling period was set to collect specific surface area data once every 5.1 minutes. If the sampling frequency was lower than the set value, the abrupt process of particle transformation from shear crushing to pressure agglomeration could not be captured. If the sampling frequency was higher than the set value, it would lead to redundant computational load on the control system and generate signal pseudo-fluctuations. Under this preset industrial electromagnetic environment, the input signal source was actively superimposed with Gaussian white noise with a signal-to-noise ratio of 20.2dB to simulate the interference of high-power motor operation.
[0036] 75.3 parts by weight of industrial steel slag and 24.7 parts by weight of silicate clinker were fed into a test mill. The initial particle grinding efficiency trajectory without grinding aid intervention was recorded as a data baseline. When the instantaneous temperature of the material reached 92.4℃, a first grinding aid containing an alkanolamine complex component was atomized and injected into the grinding equipment. The alkanolamine functional groups acted as interface chemical modifiers, inducing lattice deagglomeration through in-situ complexation reactions with the iron and aluminum cations on the surface of the steel slag glass. The intermediate state data measured at this time showed that the defect density on the particle surface decreased from the initial... Leap to The increase in this value reflects the chemical shearing effect of the first grinding aid within the thermodynamic energy barrier crossing range. During particle size monitoring, the system simultaneously extracts the characteristic particle size corresponding to the cumulative distribution volume reaching 60% and the characteristic particle size corresponding to the cumulative volume reaching 10% from the output of the online particle size analyzer. The ratio of the two values is directly defined as the uniformity coefficient. By comparing the difference of this uniformity coefficient in adjacent monitoring cycles and dividing it by the monitoring time interval, the slope of the change characterizing the deterioration trend of the particle size distribution can be obtained.
[0037] As the grinding process progressed, the online particle size analyzer detected that the specific surface area of the material reached 382.5. The subsequent growth curve exhibits non-linear saturation characteristics, at which point the calculated particle grinding efficiency factor... The system exhibited a monotonous decline for three consecutive sampling periods, with a cumulative decrease of 18.2%, indicating that it had reached a performance inflection point. This triggered the injection of a second grinding aid. The long side chains of polycarboxylic acid, acting as a steric hindrance locking component, formed a 2.3 nm to 4.8 nm physical adsorption layer on the particle surface, preventing the aggregation of fine particles induced by van der Waals forces. In contrast, the control group, using a single-addition composite grinding aid, under the same energy input, suffered from insufficient temporal decoupling, leading to thermal decomposition of the grinding aid component in the early stages and insufficient steric hindrance in the later stages, resulting in a final specific surface area of only 421.6 mm. The solid waste-based cement ultimately obtained from the sample group of this invention has a specific surface area of 512.4. .
[0038] The solid waste-based cement prepared by this invention achieved a 3-day compressive strength of 24.6 MPa, which is 35.4% higher than that of the control sample. Boundary tests by changing the injection temperature of the first grinding aid revealed that when the injection temperature is below 85.0℃, the chemical complexation reaction rate is limited by the kinetic energy barrier, resulting in no increase in early strength. However, when the temperature exceeds 105.0℃, the amine components undergo oxidative deactivation, leading to a decrease in the modification activation index. The gradient verification results above indicate that the temperature threshold band from 85.0℃ to 105.0℃ is a working window that balances chemical bond breaking and component stability. This is confirmed by the modified activation index formula. The correlation between method parameters and physical phenomena in solid waste resource utilization treatment was established, among which, The activation index is the modified value. For the increase in specific surface area, The activation energy of the structure The gas constant is... This refers to the instantaneous temperature during grinding.
[0039] Example 3: This example combines Figures 1 to 2 This document describes a method for preparing solid waste-based low-clinker cement modified with a grinding aid, as follows: Figure 1 As shown, step S101 obtains the proportioned solid waste and clinker and sends them into the grinding system. Then, step S102 starts grinding and collects instantaneous temperature data of the microenvironment. Next, step S103 adds the first grinding aid to change the crystal structure when the temperature reaches the target. Then, step S104 collects the specific surface area and power consumption to calculate the grinding efficiency factor. Then, step S105 adds the second grinding aid to inhibit fine powder agglomeration when the efficiency drops. Finally, step S106 continues grinding until the specific surface area of the material reaches the target range.
[0040] like Figure 2 As shown, the system data flow begins with the reading of cumulative power consumption data, specifically the real-time extraction of the main motor's energy consumption characteristics. Simultaneously, the instantaneous specific surface area is collected and monitored in real time by an online particle size analyzer. The above two data streams converge into the particle grinding efficiency factor calculation node to characterize the dynamic evolution of grinding efficiency. The calculation results flow to the monotonically decreasing state verification stage to perform trend determination for three consecutive sampling cycles. When the route determination is that the trend condition is met, it enters the cumulative reduction critical value comparison stage to determine whether the reduction exceeds the preset 15%. If the branch determination of the monotonically decreasing state verification or the cumulative reduction critical value comparison stage is that the critical reduction has not been reached, the control flow is fed back to the previous cumulative power consumption data reading node to form a closed loop. If the cumulative reduction critical value comparison result is a trigger determination, it enters the second grinding aid injection trigger node to implement the stepwise intervention of polycarboxylic acid dispersion components, and then flows to the physical isolation layer construction terminal stage to inhibit fine powder agglomeration behavior.
[0041] Example 4: In a low-clinker cement production scenario utilizing converter steel slag for full resource utilization, when the system faces the dilemma of excitation parameter deviation caused by fluctuations in the grindability of different batches of solid waste, this technical solution achieves digital reconstruction of the grinding efficiency evolution trajectory through online calibration of key monitoring indicators; to eliminate the uncertainty in the grinding efficiency determination process, the grinding efficiency factor of the material participating in the logical operation is... The initialization definition is implemented, and this factor is determined by the instantaneous active power of the main motor of the grinding equipment. Material throughput per unit time of the system and the ratio of coarse powder returned by the classifier It was jointly determined that the system acquires the output of the active power sensor installed in the main motor control cabinet. The data, with a measurement accuracy of no less than 0.5, is simultaneously read from the output of the feed scale. Signals, and using formulas Calculate the material grinding efficiency factor, where, This is the material grinding efficiency factor. This refers to the flow rate of material entering the mill. The reflux ratio of the air classifier. The system calculates the instantaneous power of the motor every 5.1 minutes, by... The first derivative of the rate of change is continuously monitored to determine the energy utilization efficiency of microcrack propagation inside the material.
[0042] In the actual grinding process of high-density, iron-rich steel slag, when the instantaneous temperature of the material is 92.5℃, the alkanolamine functional groups in the first grinding aid react with the exposed surface layer of the steel slag. and Cations undergo electrostatic attraction to form stable chelate rings. This modification induces a decrease in the surface hardness of the solid waste particles, and as the grinding process progresses to the later stages, the specific surface area of the material reaches 385.2. The result calculated at this time The numerical value deviated from the linear growth trajectory. When the factor showed a monotonically decreasing trend for three consecutive sampling periods with a cumulative decrease of 18.2%, it was confirmed that the fracture energy consumption of the powder particles was lower than the increase in Gibbs free energy on their surface. Van der Waals forces between particles dominated the interfacial behavior and triggered secondary agglomeration. At this point, the injection of the second grinding aid was triggered. The long side chain structure of the polycarboxylic acid component rapidly occupied the activated lattice defect sites under shear stress. Its adsorption energy at these sites was 12.5 kJ / mol higher than that of water molecules, thereby constructing a steric hindrance with a thickness of 3.2 nm on the material surface. The layer cuts off the gravitational pathways between particles; the final solid waste-based low clinker cement, while maintaining a clinker content of 24.8%, has a 28-day compressive strength of 52.6 MPa, and the volume frequency of particle size distribution in the range of 3 μm to 32 μm is 72.4%. This state corresponds to the expected effect of the technical solution on the activation of solid waste. By introducing an efficiency evaluation index based on the correlation between power consumption and material flow, the efficiency reduction of 18.2% is taken as the physical critical point for triggering spatial steric hindrance locking, and the causal relationship from the evolution of microscopic surface energy to macroscopic process adjustment in the resource-based treatment of solid waste is established.
[0043] Example 5: In scenarios involving the co-processing of multi-source industrial solid waste, to determine the predetermined mass ratio in the method, a material ratio calibration procedure based on the pre-evaluation of the activity modulus is initiated. Mass fraction data of calcium oxide, magnesium oxide, silicon dioxide, and aluminum oxide in industrial steel slag are collected, and their alkalinity modulus is calculated. When detected When the strength is in the range of 2.1 to 2.5, the mass ratio of industrial steel slag to silicate clinker is set to 3:1. Three groups of mortar specimens with different ratios are prepared and their 28-day activity strength is measured. If the measured activity strength is lower than 90.5% of the target strength, the amount of silicate clinker is increased by 2.0% per step until the activity strength returns to the preset strength envelope range, thereby establishing the optimal input benchmark for specific material composition.
[0044] In a continuously operating closed-circuit grinding system, to ensure the effective placement of the first and second grinding aids on the newly formed cleavage surfaces of the particles, an injection compensation program based on atomization pressure is initiated, and the system monitors the outlet pressures of the first and second dosing pumps. and compare it with the preset pressure reference. A comparison was conducted, in which, For pump outlet pressure, The preset pressure is used to detect... When the injection pressure is below the lower limit of 0.35 MPa, the system automatically increases the compressed air flow rate of the atomizing nozzle to maintain the droplet size distribution range of 15.0 μm to 45.0 μm, preventing the grinding aid component from causing local concentration overload due to dripping, thereby ensuring that the polycarboxylic acid dispersion component occupies the active sites generated by lattice depolymerization, and suppressing the powder agglomeration behavior by maintaining the interfacial adsorption energy gradient.
[0045] In a low-clinker cement production scenario utilizing converter steel slag for full resource recovery, to address the differences in thermodynamic energy barriers caused by fluctuations in the mineral phase composition of different batches of raw materials, an offline calibration process was initiated to determine the structural activation temperature threshold band of the material for that batch. Under controlled experimental conditions, an isothermal gradient grinding test was conducted on a 10.0 kg steel slag sample, recording the increase in specific surface area of the particles every 5.0℃. and using the formula Fitting the structural activation energy With the instantaneous temperature of grinding The response curve, where, The activation index is the modified value. For the increase in specific surface area, The activation energy of the structure, Let be the gas constant, with a value of 8.314. , The instantaneous grinding temperature is used to define the temperature point corresponding to the maximum value of the first derivative of the modification activation index as the injection trigger temperature of the first grinding aid, so that the chemical complexation reaction is initiated in the energy level range where the degree of lattice distortion reaches its peak.
[0046] When the system faces a deviation in the surface energy evolution trajectory of powder caused by fluctuations in the moisture content or initial temperature of the feed material, a system based on the feed material flow rate is established. With the instantaneous power of the motor A coupled dynamic compensation model is used to correct the judgment limit of the material grinding efficiency factor. The on-site baseline calibration program is started within 30.2 minutes before the grinding equipment starts running with material to obtain the instantaneous power of the motor under different feed rates. The fundamental frequency data, combined with the material grinding efficiency factor measured by an online particle size analyzer, was used. Initial value, using formula Calculate, where, This is the material grinding efficiency factor. This refers to the flow rate of material entering the mill. The reflux ratio of the air classifier. Given the instantaneous power of the motor, an efficiency reduction correlation matrix was established for different abrasiveness levels. This allowed for adaptive adjustments to the 18.2% efficiency reduction threshold based on batch-to-batch differences in material abrasiveness, ultimately maintaining the specific surface area of the resulting solid waste-based cement at a stable 510.5. Specifically, the internal calibration logic of the efficiency reduction correlation matrix is as follows: the average main motor base frequency power during the baseline calibration period is extracted as the abrasiveness mapping input. When the base frequency power is in the range of 70% to 80% of the rated full load power, it corresponds to a low abrasiveness level, and the matrix output sets the reduction threshold to 15.0%; when it is in the range of 80% to 90%, it corresponds to a medium abrasiveness level, and the matrix output linearly interpolates the reduction threshold to 18.2%; when it is greater than 90%, it corresponds to a high abrasiveness level, and the matrix output locks the reduction threshold to 20.0%. The matrix parameters are derived from the regression statistics of historical grinding calibration big data of 100,000 tons.
[0047] Example 6: In a low-clinker cement production scenario utilizing high-magnesium converter steel slag for full resource recovery, to address the activation blind zone caused by uneven material hardness and chemical activity, a benchmark parameter calibration program for this batch of material was initiated. A 50.0 kg sample was extracted from the material to be ground and dried to constant weight at 105.0℃ in a constant-temperature oven. Isothermal gradient grinding was then performed using a laboratory mill equipped with a thermocouple array. The mill's internal pressure was maintained at 0.1 MPa. The particle specific surface area was recorded to reach 450.0 within a 5.0℃ gradient between 60.0℃ and 120.0℃. Required time constant And according to the formula Establish the grinding rate constant With thermodynamic temperature The correlation matrix, where, Let be the grinding rate constant. Pre-exponential factor, The activation energy of the structure, Let be the gas constant, with a value of 8.314. , For absolute temperature, linear regression was performed on 12 sets of temperature data points using the least squares method. Once the correlation coefficient was determined... When the value is greater than 0.98, the fitted value at this time will be... The numerical values serve as preset parameters for the global controller, establishing the threshold for determining the transition from an inert phase to an active phase in solid wastes with different mineral compositions at the methodological level.
[0048] When the system faces conditions such as fluctuations in the main motor current of the classifier or sudden changes in the classifying air volume causing deviations in the grinding cycle load, a system based on the reflux ratio is implemented. Real-time correction compensation algorithm to maintain material grinding efficiency factor To ensure stability, a differential pressure transmitter installed at the circulating air duct is used to collect the circulating air pressure. The transmitter has a measurement accuracy of 0.2% of full scale and will With the rotation speed of the air classifier Mapped to real-time cyclic load offset and the corresponding compensation operator To dynamically adjust the judgment limit of the material grinding efficiency factor, wherein, For compensation coefficient, This is the sensitivity factor, with a value set between 0.05 and 0.15. This is the cyclic load offset; if the instantaneous power of the motor is monitored... If a pulse transition exceeding 15.0% occurs, the system automatically switches to emergency safety mode and fixes the injection frequency of the first dosing pump at 45.0Hz until the signal mean of five consecutive sampling cycles returns to within one standard deviation. The feedback calibration procedure based on physical sensor data eliminates false triggers caused by sensor zero-point drift or instantaneous agglomeration of raw materials, and the particle size deviation of the produced cement powder is maintained within ±2.0μm.
[0049] The embodiments of this application have been described above with reference to the accompanying drawings. Unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other. This application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit of this application and the scope of protection of this invention, and all of these forms are within the protection scope of this application.
Claims
1. A method for preparing solid waste-based low-clinker cement modified with grinding aid, characterized in that, Includes the following steps: Step S101: Obtain industrial solid waste and silicate clinker in a predetermined mass ratio and feed them into a closed-circuit grinding system. Step S102: Start the closed-circuit grinding system to grind the material, and use the temperature sensor set at the outlet of the closed-circuit grinding system to collect instantaneous temperature data in real time, which characterizes the thermal state of the microenvironment of the material grinding. Step S103: Compare the instantaneous temperature data with the preset structural activation temperature threshold band of 85°C to 105°C. When the instantaneous temperature data reaches the structural activation temperature threshold band, add a first grinding aid containing an alcohol amine complex component into the closed-circuit grinding system to change the lattice structure of the fresh cleavage surface generated by industrial solid waste. Step S104: Collect the instantaneous specific surface area of material particles in the closed-circuit grinding system and the cumulative power consumption data of the main motor of the closed-circuit grinding system, and use this data to calculate the particle grinding efficiency factor that characterizes the dynamic evolution of grinding efficiency. Step S105: When it is determined that the particle grinding efficiency factor shows a monotonically decreasing state for three consecutive sampling cycles and the cumulative decrease exceeds 15%, a second grinding aid containing polycarboxylic acid dispersion components is added to the closed-circuit grinding system to inhibit the agglomeration behavior of fine powder by using the physical isolation layer generated on the surface of industrial solid waste particles by the second grinding aid. Step S106: Continue grinding until the specific surface area of the material at the outlet of the closed-circuit grinding system reaches 400 m². 2 / kg to 550m 2 The target range is between / kg.
2. The method for preparing grinding aid modified solid waste-based low-clinker cement according to claim 1, characterized in that, In step S103, the injection flow rate of the first grinding aid is adjusted according to the real-time rise slope of the instantaneous temperature data, and includes the following sub-steps: Step S1031, measuring the temperature rise amplitude of the instantaneous temperature data per unit time and determining the corresponding thermal balance coefficient; Step S1032, adjusting the metering pump frequency of the first grinding aid so that the addition rate of the first grinding aid matches the dissolution rate of the active components in the industrial solid waste.
3. The method for preparing grinding aid modified solid waste-based low-clinker cement according to claim 1, characterized in that, In step S101, the total weight of industrial solid waste and silicate clinker is calculated as 100 parts, including 60 to 85 parts of industrial solid waste and 15 to 40 parts of silicate clinker; the industrial solid waste includes granulated blast furnace slag powder, fly ash, steel slag powder and desulfurized gypsum.
4. The method for preparing grinding aid modified solid waste-based low-clinker cement according to claim 1, characterized in that, In step S103, the first grinding aid is injected through the spray atomization device of the closed-circuit grinding system, and its atomization pressure is controlled between 0.4MPa and 0.6MPa, so that the first grinding aid is uniformly covered on the fresh cleavage surface.
5. The method for preparing solid waste-based low-clinker cement modified with grinding aid according to claim 1, characterized in that, In step S105, the second grinding aid includes a polycarboxylic acid dispersion component, polyethylene glycol, and lignin sulfonate; the second grinding aid neutralizes the residual charge on the surface of industrial solid waste particles through its polar functional groups, thereby blocking the interference between the adsorption positions of the first grinding aid and the second grinding aid on the fresh cleavage surface.
6. The method for preparing grinding aid modified solid waste-based low-clinker cement according to claim 1, characterized in that, In step S104, the instantaneous specific surface area is monitored by an online particle size analyzer. The monitoring frequency is once every 3 to 10 minutes, and includes the following sub-steps: comparing the particle size distribution in adjacent monitoring periods, calculating the slope of the change in uniformity coefficient, and using it to determine whether the material has entered the secondary agglomeration stage dominated by interfacial energy from the mechanical crushing stage.
7. The method for preparing grinding aid modified solid waste-based low-clinker cement according to claim 1, characterized in that, The closed-circuit grinding system includes a vertical mill or a ball mill; in step S102, the filling rate of the grinding media in the closed-circuit grinding system is controlled to be 25% to 35%, and the average residence time of the material inside the closed-circuit grinding system is controlled to be 25 min to 45 min.
8. The method for preparing grinding aid modified solid waste-based low-clinker cement according to claim 1, characterized in that, After grinding is completed in step S106, the resulting material is introduced into a cold air circulation device for rapid cooling. The cooling rate is controlled to be no less than 15℃ / min, so that the active defect sites formed inside the industrial solid waste are physically locked when the temperature drops below 40℃.
9. The method for preparing grinding aid modified solid waste-based low-clinker cement according to claim 1, characterized in that, The cement products obtained meet the following performance requirements: 3-day compressive strength not less than 20 MPa, 28-day compressive strength not less than 42.5 MPa, and the 28-day hydration activity index of industrial solid waste in the product is not less than 85%.
Citation Information
Patent Citations
Coal-based solid waste cementing material for coal mine filling engineering as well as preparation method and application of coal-based solid waste cementing material
CN120136461A